A study on resting-state functional near-infrared spectroscopy in patients with different outcomes of prolonged disorders of consciousness - Liang, Yanli; Liang, Xin; Li, Yijiang; Wang, Chaowen; Bi, Yinuo; Xue, Yuan; Jiang, Wenyu (Frontiers in Neurology, 2025)
BackgroundTo explore the characteristics of resting-state functional connectivity in patients with different outcomes of prolonged disorders of consciousness (pDoC) by studying resting-state near-infrared imaging in patients with pDoC.Methods60 patients with pDoC were processed with resting-state near-infrared imaging and divided into unresponsive wakefulness syndrome/vegetative state (UWS/VS) group, minimally conscious state (MCS) group and escape minimally conscious state (EMCS) group according to the post-treatment state of consciousness, to analyze the difference of resting-state functional connectivity in patients with different outcomes of patients with pDoC.ResultsFunctional connectivity (FC) between frontal lobe and left occipital lobe, frontal lobe and right occipital lobe, and left and right occipital lobes decreased in the UWS/VS group compared with the MCS group; functional connectivity between frontal lobe and left occipital lobe, frontal lobe and right occipital lobe, and left and right occipital lobes decreased in the UWS/VS group compared with the EMCS group; functional connectivity did not show any significant difference between the EMCS and MCS groups; and functional connectivity was more centralized in the MCS group and EMCS group.ConclusionDifferent outcomes of patients with pDoC have different degrees of decline in functional connectivity between frontal lobe and occipital lobe and between occipital lobe, resting-state functional near-infrared spectroscopy has a certain reference significance for the prognosis of patients with pDoC, and it is helpful for exploring the exploration of the conscious residual brain areas.